New insights into the role of dietary triglyceride absorption in obesity and metabolic diseases - Li, Xiaojing; Liu, Qiaohong; Pan, Yuqing; Chen, Si; Zhao, Yu; Hu, Yiyang (Frontiers in Pharmacology, 2023)
The incidence of obesity and its associated metabolic diseases is increasing globally, adversely affecting human health. Dietary fat, especially triglycerides (TG), is an important energy source for the body, and the intestine absorbs lipids through a series of ordered and complex steps. Long-term high-fat diet can dysregulate intestinal function and induce obesity and metabolic disorders. Therefore, regulating dietary TG absorption is a promising therapeutic strategy. In this review, we discuss the processes of dietary TG hydrolysis, fatty acid uptake, TG resynthesis, chylomicron assembly, trafficking, and secretion by intestinal epithelial cells, as well as potential targets of this process that may influence dietary fat-induced obesity and metabolic disease. We also mention the possible shortcomings and deficiencies of modulating dietary lipid absorption targets to provide a better understanding of their administrability as drugs in obesity and related metabolic disorders.